Patterns of ECG Manifestations in Dengue Infection - Tabassum, Chowdhury Tamanna; Arifuzzaman, Md; Sayem, Mohammad; Mostafa, Tanvir; Bodruddoza, Kazi; Kabir, Ahmedul (Journal of Medicine, 2023)
Background: Dengue fever has emerged as one of the most common viral diseases in the world. The clinical manifestation ranges from mild febrile illness to severe disease such as dengue hemorrhagic fever and dengue shock syndrome. Dengue is known to affect various systems. So, different aspects of disease need to be explored. Cardiac involvement in dengue fever is not uncommon and has been reported in literature. ECG is widely used as a screening tool not only because it is easily available but also due to its ability to indicate cardiac involvement. Objective: The aim of the study was to determine the patterns of ECG changes and their frequency in a cohort of patients with dengue fever (DF) and dengue hemorrhagic fever (DHF) along with the association of ECG changes with severity of dengue infection and clinical manifestation of cardiac involvement. Method: We conducted a cross-sectional observational study involving 50 patients with dengue fever and dengue hemorrhagic fever, admitted in Medicine department of Dhaka Medical College Hospital, Dhaka from 1st October, 2017 to 31st March, 2018. Admitted patients with high grade fever and positive Dengue IgM, NS1 AG or RT-PCR were included. Patients with electrolyte abnormalities, preexisting heart disease, drugs interfering with heart rhythm were excluded from study. The Standard 12 lead ECG was carried out in study patients on 3rd day of disease onset and on the day of discharge after disease recovery. Frequency & pattern of ECG changes like heart rate, rhythm, P wave, T wave, ST segments and QRS complex were analyzed and recorded. Statistical analysis was done using SPSS 25 on windows 10. Categorical and numerical data’s were expressed as frequencies and percentage. Cross tabulation was done between DF and DHF with different ECG findings. To establish the significance of various findings and association in between variables chi-square analysis, Pearson correlations were done in all cases. P value < 0.05 considered significant Result: Total 50 patients with dengue fever were enrolled, 39 patients (78%) were diagnosed as dengue fever and 11 patients (22%) were diagnosed as dengue hemorrhagic fever (DHF). Mean age of the patient was 33.08 ± 9.79 years. Male – female ratio of 1.5:1 fever was noted in all 50 patients (100%), myalgia (94%), headache (84%), skin rash (82%), & retro-orbital pain(54%), vomiting (26%), only 3 patients (6%) complained about abdominal pain. Only 4 patients had cardiac symptoms. 3 patients complained about palpitation and only 1 patient had symptom of chest pain and dyspnea. In most of the patients, (34 in number, 68%) ECG was normal. Only 16 patients (32%) had abnormal findings in ECG. 9 patients (18%) had bradycardia, 3 patients (6%) had tachycardia, 2 Patient (4%) had T Inversion and 1 patient (2%) had ST elevation and 1 patient (2%) had ST depression. Among total 16 abnormal ECG, predominant finding was bradycardia (>50% of abnormal ECG). P value is <0.01. Correlation of ECGs with clinical severity (Dengue fever and Dengue Hemorrhagic fever) found no statistically significant association (P value is 0.725). J MEDICINE 2023; 24(2): 119-124